Theoretical concepts of photocatalysis - Khan, Mohammad Mansoob (Amsterdam, Netherlands : Elsevier, 2023)
'Theoretical Concepts of Photocatalysis offers a concisely structured and systematic overview of photocatalysis as well as explores the theory and experimental studies of charge-carrier dynamics in photocatalysis. This book introduces the fundamental concepts of photocatalytic reactions involving different types of photocatalysts for various applications such as treatment of polluted water, wastewater, polluted air, food packaging, and biomedical and medical fields. This book also details the chemistry of visible light-induced photocatalysis, shown by different classes of photocatalysts for novel energy and environment-related applications. Photocatalysis using different types of photocatalysts (such as metal oxides, chalcogenides, their composites, etc.) is a green technology that has been widely applied for environment remediation and energy production. Its significant advantages, such as low cost, high efficiency, stability, and harmlessness, are discussed alongside future perspectives and challenges of photocatalysis. Focusing on nanostructure control, synthesis methods, activity enhancement strategies, environmental applications, and perspectives of semiconductor-based nanostructures. This book offers guidelines for designing novel semiconductor-based photocatalysts with low cost and high efficiency to meet the demands of the efficient utilization of solar energy in the area of energy production and environment remediation.'--Page 4 of cover.
Includes bibliographical references and index.
Keywords: Photocatalysis